2009
DOI: 10.1200/jco.2009.24.3675
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of a Granulocyte-Macrophage Colony-Stimulating Factor–Encoding, Second-Generation Oncolytic Herpesvirus in Patients With Unresectable Metastatic Melanoma

Abstract: The 26% response rate, with durability in both injected and uninjected lesions including visceral sites, together with the survival rates, are evidence of systemic effectiveness. This effectiveness, combined with a limited toxicity profile, warrants additional evaluation of JS1/34.5-/47-/GM-CSF in metastatic melanoma. A US Food and Drug Administration-approved phase III investigation is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
426
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(452 citation statements)
references
References 22 publications
13
426
0
5
Order By: Relevance
“…Recently, sipuleucel-T (Provenge, Dendreon, Seattle, WA, USA), indicated for patients with metastatic castration-resistant prostate cancer, received FDA's approval as the first therapeutic cancer vaccine. 5 In addition, extensive Phase II clinical trials have demonstrated that the oncolytic herpes simplex virus talimogene laherparepvec (T-Vec, Amgen Inc., Thousand Oaks, CA, USA) 6 and vaccinia virus JX-547 (Pexa-Vec, Jennerex Biotherapeutics, Inc., San Francisco, CA, USA), 7 both of which carry the gene encoding the immunostimulatory cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF), hold great promise for the treatment of advanced cancer patients. Furthermore, cytotoxic T-cell responses directed against oncolytic virus-infected cancer cells have been identified as an essential factor in the process of destruction of cancer.…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, sipuleucel-T (Provenge, Dendreon, Seattle, WA, USA), indicated for patients with metastatic castration-resistant prostate cancer, received FDA's approval as the first therapeutic cancer vaccine. 5 In addition, extensive Phase II clinical trials have demonstrated that the oncolytic herpes simplex virus talimogene laherparepvec (T-Vec, Amgen Inc., Thousand Oaks, CA, USA) 6 and vaccinia virus JX-547 (Pexa-Vec, Jennerex Biotherapeutics, Inc., San Francisco, CA, USA), 7 both of which carry the gene encoding the immunostimulatory cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF), hold great promise for the treatment of advanced cancer patients. Furthermore, cytotoxic T-cell responses directed against oncolytic virus-infected cancer cells have been identified as an essential factor in the process of destruction of cancer.…”
Section: Open Questionsmentioning
confidence: 99%
“…Indeed, the results of clinical trials of the GM-CSF gene-harboring oncolytic vaccinia virus JX-594 and the GM-CSF gene-harboring oncolytic herpes virus talimogene laherparepvec demonstrated that a clinical benefit can be accomplished by combined respective oncolytic activity with the recruitment of immune cells. 6,7,131 The combination of adoptive T-cell therapy with oncolytic viruses is shown to elicit an increased antitumor effect. 131,132 Collectively, the design of combinatorial therapies of oncolytic viruses with immunotherapeutic modalities may 136,137 and (6) directly targets not only the primary tumor but also metastases.…”
Section: Strategies To Enhance the Potentials Of Icd Induced By Oncolmentioning
confidence: 99%
“…One-year overall survival rates of 61, 58 and 48% for all patients, all stage IV patients and stage IV M1c patients, respectively. 133 A recently published meta-analysis of 2100 patients with stage IV metastatic melanoma reported a 1-year overall survival rate was 25.5%. The median survival time is 16 þ months for all patients treated with OncoVEX GM-CSF as well as for the stage IV subset; the median survival time in the meta-analysis was 6.2 months (95% confidence interval, 5.9 months to 6.5 months).…”
Section: Herpes Simplex Virus (Hsv)mentioning
confidence: 99%
“…Several HSV-1 vector expressing GM-CSF have been used to treat experimental tumours [140, 160, 192, 201, 202] and some of them are in clinical trials [203-205]. Most of the oncolytic HSVs analyzed have been based on serially passaged laboratory strains of HSV.…”
Section: Hsv-1 Based Vectors For Cancer Gene Therapymentioning
confidence: 99%
“…Moreover, in a model of mouse lymphoma, mice cured with this virus were protected against further tumour challenge [160]. OncoVex has demonstrated promising results both in phase I/II dose escalation study for head and neck squamous cell cancer [204] and in phase II clinical trial for unresectable malignant melanoma [203, 205]. In spite of the promising findings obtained in clinical trials, using OncoVex, the expression of GM-CSF gave contradictory results in different tumour models [206].…”
Section: Hsv-1 Based Vectors For Cancer Gene Therapymentioning
confidence: 99%